Phosphorus Leaching from an Organic and a Mineral Arable Soil in a Rainfall Simulation Study. Issue 3 (1st May 2018) - Riddle, Matthew; Bergström, Lars; Schmieder, Frank; Kirchmann, Holger; Condron, Leo; Aronsson, Helena
Abstract : Phosphorus derived from agricultural systems has been found to cause eutrophication of surface waters. To combat this, the specific location of soil profile P release is necessary for development of effective mitigation strategies. This paper describes a P leaching study of two Swedish arable soils, an organic (Typic Haplosaprist) and a mineral soil (Typic Hapludalf), both with high P content. Undisturbed soil columns isolated 0‐ to 20‐, 20‐ to 40‐, 40‐ to 60‐, and 60‐ to 80‐cm depth intervals. These were placed in a rainfall simulator and subjected to four 50‐mm rainfall events to identify the origin of P leachate as a function of soil depth interval and physicochemical properties. Phosphorus losses were greatest from the two uppermost layers of both soils after 200 mm of artificial rainfall was applied at 5 mm h −1 . Total P concentration in leachate from the 0‐ to 20‐cm layer ranged from 2.1 to 8.8 mg L −1 for the mineral and 3.7 to 10.3 mg L −1 from the organic soil, with most (95–100%) in dissolved reactive P form. Degree of P saturation correlated well with total P leaching losses from the organic soil ( R = 0.84) but not the mineral soil ( R = 0.69), suggesting that the presence of Al and Fe (hydr)oxides has a stronger influence on P leaching in the organic soil. Results indicate that both soils have the potential to contribute concentrations of P above those known to cause eutrophication of surface waters. Core Ideas: The majority of P leached from both soils was from the top 20 cm, in DRP form. Phosphorus concentrations in leachate were higher from the organic than the mineral soil. Degree of P saturation correlated well with P leached from the organic soil. High rainfall application promoted losses of P potentially complexed to DOC and Fe or Al. Both soils leached concentrations of P above those known to cause eutrophication.